Pulmonary function in workers exposed to diesel exhausts: the effect of control measures - Ulfvarson, U; Alexandersson, R; Dahlqvist, M; Ekholm, U; Bergström, B (American journal of industrial medicine, 1991)
To assess the protective effect of exhausts pipe filters or respirators on pulmonary function, 15 workers in a tunnel construction site, truck and loading machine drivers, rock workers, and others were studied. The total and respirable dust, combustible matter in respirable dust, carbon monoxide, nitrogen monoxide and nitrogen dioxide were measured for each subject during entire work shifts. The effect of the exposure on the lung function variables was measured by dynamic spirometry, carbon monoxide single breath technique, and nitrogen single breath wash-out. The exhaust pipe filtering had a protective effect, directly discernible in the drivers on vital capacity and FEV1.0 and for the whole group on FEV% and TLco. The dust respirators had no effect, probably because of the difficulties in correctly using personal protection under the circumstances in the tunnel. In the absence of a true exposure assessment, control measures for diesel exhausts can be tested by medical effect studies. Catalytic particle filters of diesel exhausts are one method of rendering the emissions less irritant, although they will not remove irritant gases. An indicator of diesel exhaust exposure should include the particle fraction of the diesel exhausts, but a discrimination between different sources of organic dust must be possible.